THE FIRST FIVE YEARS OF THE SERBIAN JOURNAL OF THE MEDICAL CHAMBER – A BRIEF OVERVIEW AND ANALYSIS: The first five years of the Serbian Journal of the Medical Chamber - Vukcevic Lackovic, Biljana (Srpski medicinski časopis Lekarske komore, 2025)
This is a brief overview of the Serbian Journal of the Medical Chamber, marking its fifth anniversary. It aims to inform the reader about the Journal in the context of other Serbian medical publications and present a concise analysis of the types of articles published and the topics covered to date, thus providing insight into what the Journal offers to both readers and authors.
Keywords: Serbian Journal of the Medical Chamber; fifth anniversary; overview